Respostas

2013-11-19T19:49:21-02:00
Não tenho absoluta certeza do que vou falar, mas acho que é isso:

a3 = 144
a6 = 486
a1 = ?

an = am.q^(n-m)
a6 = a3.q^(6-3)
486 = 144.q^3
q^3 = 3,3
q = 1,5
.
an = a1.q^(n-1)
144 = a1.1,5^2
2,25.a1 = 144
a1 = 64
2013-11-19T20:28:46-02:00
A_3 = 144
a_6 = 486

a_3 = a_1*q^2
a_6 = a_1*q^5

a_1*q^2 = 144  >>>>>> a_1 = 144/q^2  (i)
a_1*q^5 = 486    (ii)
Substituindo (i) em (ii)
(144/q^2)*q^5 = 486
144q^3 = 486
q^3 = 486/144
q = raiz cúbica de (486/144) = 1,5
Substituindo q em (i) temos:
a_1 = 144/1,5^2 = 144/2,25 = 64